Work Requirements That Don't Work - Latham, Stephen R. (The Hastings Center report, 2018)
Early in 2018, the Trump administration's Centers for Medicare and Medicaid Services issued a guidance letter outlining a new and controversial kind of Medicaid waiver proposal. The administration invited states to propose waivers that would impose work (or other “community engagement”) requirements as a condition of eligibility for Medicaid. The Trump administration and state proponents of work requirements want to force able-bodied Medicaid beneficiaries into the workplace. Critics allege that this is because they mistakenly believe that low-income individuals are not working because they're lazy or because aid programs provide them with a disincentive to work. Proponents respond that the requirements can lower the public programs' costs while helping its recipients. Medicaid data seems to show that the work-requirement proposals are a solution in search of a real-life problem.